PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TALKING STICK UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS III SDN 06 KADUR KECAMATAN RUPAT UTARA - Zaharah Zaharah; Otang Kurniaman; Lazim N Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The problem of this research because low of IPS study result of the third grade students at SDN 06 Kadur, Rupat Utara subdistrict. KKM stated at school was 70. From 26 students, only 14 students that reached KKM (53,85%), whereas student did not still reach KKM yet were 12 students (46,15). With score mean of class was 64,04. For solving the problem, there for the researcher implement learning model of talking stick type. The goal of research was for increasing IPS study result of the third grade students at SDN 06 Kadur by implementing learning model of talking stick type. The research was classroom action research. The technique of collecting data by using observation and test. The result of research was collected at first meeting of cycles, the teacher’s activity on classification “enough” (54,17%), after at second meeting, that known the teacher’s activity on classification “good”(70,83%). at first meeting of cycles II, teacher’s activity on classification ”good”(79,16%), after at second meeting teacher’s activity on classification “very good”(87,60%). At first meeting cycle I, students’ activity on classification “poor”(45,83%), at second meeting students’ activity on classification ”good” (79,16%). At first meeting of cycles II, the students’ activity on classification “very good”(83,33%). At second meeting students’ activity on classification“very good”(91,66). At cycles 1 known that total of students reached KKM were 18 students (73,08%) with mean score 75,19. At cycles II, total of students reached KKM were 23 students (88,46%) with mean score 84,04. Based on this research can be concluded that by implementing cooperative learning model of talking stick type can increase IPS study result of the third grade students at SDN 06 Kadur sub-district Rupat Utara.Keywords: Cooperative of talking stick type, social studies students achievement